Edukasi Pencegahan Stunting Melalui Pemberian ASI Eksklusif Pada Masyarakat: Edukasi Pencegahan Stunting Melalui Pemberian ASI Eksklusif Pada Masyarakat - Dewina Susanti; Rika Dewi (Ahmar Metakarya: Jurnal Pengabdian Masyarakat, 2022)
Aceh is one of the provinces with the highest prevelance of stunting above the national figure with a stunting prevelance of 37%. During the covid_19 pandemic, the community’s space to seek sustenance was hampered, thus affecting the economy to fulfill nutritional sources for children. This activity aims to increase public knowledge about the dangers of stunting and the benefits of exclusive breastfeeding which is rich in nutrition and cheap in stunting prevention. The activities carried out were in the form of educating the benefits of exclusive breastfeeding and the nutrients contained in breast milk as well as demonstrations of Oxytocin massage to facilitate breast milk production for mothers in the community in Meunasah Kulam village, Mesjid Raya district, Kabupaten Meunasah Kulam, Aceh Besar, Aceh Province. The results of this service, mothers can know the importance of exclusive breastfeeding to reduce the incidence of stunting. It is hoped that after public education, especially mothers who have babies and women of childbearing age, husband and wife can apply exclusive breastfeeding to reduce the incidence of stunting.